The Roles of TGF-β Signaling in Cerebrovascular Diseases - Zhang, Yizhe; Yang, Xiao (Frontiers in Cell and Developmental Biology, 2020)
Cerebrovascular disease is one of the leading causes of death worldwide, however, little can be done to prevent or treat cerebrovascular disease to date. The transforming growth factor-β (TGF-β) signaling pathway plays crucial and highly complicated roles in cerebrovascular development and homeostasis, and dysregulated TGF-β signaling contributes to cerebrovascular diseases. In this review, we provide an updated overview of how the TGF-β signaling functions in the cerebrovascular system under physiological and pathological conditions. We discuss the current understanding of TGF-β signaling in cerebral angiogenesis and the maintenance of brain vessel homeostasis. We also review how the disharmony of endothelial TGF-β signaling triggers or promotes the progression of cerebrovascular diseases. At last, we briefly discuss the potential of targeting TGF-β signaling to treat cerebrovascular diseases.